Commercial formulation amendment transiently affects the microbial composition but not the biogas production of a full scale methanogenic UASB reactor. Issue 24 (27th October 2020) - Cabezas, A.; Bovio, P.; Etchebehere, C.
ABSTRACT: The treatment of dairy wastewater in methanogenic reactors cause several problems due to their high lipid content. One strategy to overcome these problems is the use of commercial formulations. Here we studied the effect of adding a commercial formulation, designed to improve fat degradation, on both the microbial community composition and reactor performance. Samples from two full-scale Up-flow Anaerobic Sludge Blanket (UASB) reactors in parallel arrangement were analysed. The commercial product was added to one of the reactors while the other was used as control. The amendment increased significantly the fat removal but an accumulation of volatile fatty acids was detected. Nevertheless, no significant differences were observed in the total Chemical Oxygen Demand (COD) removal and biogas production between reactors. A significant change in the bacterial community was not detected by 16S rRNA gene Terminal Restriction Fragment Length Polymorphism (T-RFLP) analysis probably due to the limitation of the technique. A strong change in the composition of the phylum Firmicutes was detected with 16S rRNA gene amplicon sequencing; however, it didn't persist during the whole operation period. The relative abundance of minor Operational Taxonomic Units (OTUs) with sequences related to syntrophic bacteria increased with the amendment. Although a better hydrolytic capacity was obtained when adding the commercial product, the overall process did not improve and no increase in biogas production was detected. Alternative strategies could be applied to avoid the accumulation of intermediary products and improve biogas production as intermittent addition of the commercial product or batch operation of reactors. GRAPHICAL ABSTRACT: UF0001